Model Test on Segmental Grouting Diffusion Process in Muddy Fault of Tunnel Engineering - Jun Liu; Qingsong Zhang; Lianzhen Zhang; Fang Peng; Zhipeng Li; Xianjie Weng (Geofluids)
In order to realize the diffusion law of segmental grouting in muddy fault of tunnel engineering, a three-dimensional grouting diffusion simulation test has been done. Three times of grouting operation have been done for three adjacent sections in grouting pipe. Grouting pressure, injection rate, soil pressure field, and seepage pressure field have been real-time monitored in three grouting stages. The effect of segmental grouting operation on soil pressure field and effective stress field has been analyzed. Results show that previous grouting operation can affect later grouting operation. Due to previous grouting operation, the grouted stratum can be compacted and grouting diffusion will conquer greater resistance in later grouting stages. Correspondingly, grouting pressure increases and injection rate decreases in the later grouting stage. There exists a limited influence range for a single grouting operation. For every grouting stage, soil pressure and effective stress in the section which the injection hole locates in are affected effectively by grouting operation. By contrast, soil pressure and effective stress in section away from injection hole are affected relatively weakly by grouting operation. With distance to injection hole increasing, compaction degree and reinforcement effect of grouted muddy fault decay in space. Multisegmental grouting method has significant advantages over single grouting method. Ineffectively compacted area by previous grouting operation can be effectively compacted by later grouting operation from adjacent injection hole. As a result, uniformity of grouting reinforcement effect can be improved, and weakly reinforcement area can be reduced.